Teorías subjetivas del bienestar en un grupo de adolescentes mayores de edad de Lima Metropolitana - Calmet Otero, Luis Pedro (2023)
The present qualitative research aimed to discuss the subjective theories of a group of older adolescents in Metropolitan Lima about what a good life means to them and how to achieve it, by analyzing them with PERMA's scientific theory of human well-being and flourishing. For this purpose, a group of participants composed of six males and four females whose average age was twenty-one years old was gathered. In-depth interviews were conducted with questions related to their definition of happiness and happiness during pandemics. The most relevant dimensions found in the subjective theories of wellbeing were organized into four thematic axes: pleasurable activities, self-fulfillment, meaningful experiences and interpersonal bonds. The global event of the COVID-19 pandemic allowed us to observe that the relevant dimensions of well-being, happiness or human flourishing, prevail even after post-traumatic events such as this health crisis, evidencing the value of factors such as relationships, the search for fulfillment and positive emotions.